Radiation and scattering properties of a novel UWB microstrip antenn - Yatong Zhou; Xin Wang; Kewen Xia (2011 6th IEEE Conference on Industrial Electronics and Applications, 2011)
In this paper, an improved microstrip and patch antenna is proposed for ultra-wideband applications. The patch of antenna combination with a semi-circular and a rectangular, the shape of wide slit on the ground is similar with the shape of the patch and then set the input impedance of 75Ω. The return loss is less than -10dB from 1GHz to 10GHz. Good dipole-like omni-directivity in azimuth plane has been shown. Finally, the relevant simulation and calculation are performed by using HFSS of ANSOFT Company. The reflection loss curve and the radiation patters of this new antenna were given.